Pengetahuan dan Sikap Keluarga Tentang Gizi Seimbang pada Anak dan Balita dalam Pencegahan Stunting - Rizza Anfhal; Supriati Supriati; Yusrial Tarihoran; Nana Erika (STIKES Columbia Asia Medan, 2025)
Family knowledge and attitudes regarding balanced nutrition in children and toddlers play a crucial role in preventing stunting. This study aims to analyze family knowledge and attitudes towards balanced nutrition and its relationship with stunting prevention in Desa Regemuk, Pantai Labu Sub-district, Deli Serdang Regency. This research used a descriptive quantitative approach with a sample of 100 families who have children aged 0-5 years. Data were collected using questionnaires containing questions about family knowledge and attitudes related to balanced nutrition. The results showed that approximately 40% of families had good knowledge about balanced nutrition, while 60% had limited knowledge. However, most families demonstrated positive attitudes towards providing nutritious food for their children. Economic factors were identified as the main barrier to implementing balanced nutrition in families with lower-middle-income status. The study concludes that to reduce stunting prevalence, there is a need to improve knowledge about balanced nutrition and provide accessible nutritious food for families in rural areas.